Impact pathways: unhooking supply chains from conflict zones-reconfiguration and fragmentation lessons from the Ukraine-Russia war - Srai Jagjit Singh; Graham Gary; Van Hoek Remko; Joglekar Nitin; Lorentz Harri (Emerald, 2025)
Purpose
The new geopolitical context being created by the Ukraine-Russia war highlights the need for structured approaches to planning and implementing unhooking strategies and developing associated supply chain reconfigurations.
Design/methodology/approach
The authors have interviewed six supply chain executives to begin the investigation of the key supply chain risks and disruptions caused by the Ukraine-Russia war.
Findings
Initial corporate responses to the Ukraine-Russia conflict were significant, perhaps unprecedented. However, as institutional, corporate and consumer sentiment influence reconfiguration responses, the authors have identified three supply chain pathways that underpin unhooking actions.
Research limitations/implications
The authors selected respondents from each different type of supply chain interaction with the conflict zone (inbound, outbound and within), covering both components/intermediate products and finished goods. Therefore the sample size was small and designed to fit in with the spirit of the pathway initiative.
Practical implications
The authors reinforce the key role of procurement and supply chain management in not just supply but also in downstream markets that can accelerate decoupling and mitigate the associated supply chain disruptions.
Social implications
The authors observe that supply chains are increasingly being weaponized, as external institutional and consumer influences necessitate companies to unhook from conflict zones, countries, or regimes. They are becoming increasingly intertwined with foreign policy.
Originality/value
The novelty of the contribution to the associated discourse is the perspective that after decades of increasing globalization and geographic dispersion of supply chains, the unhooking effort is not limited to a firm and its internal operations but involves multiple stakeholders. For instance, the full extent of the complex linkages of supply chains, networks and relationships that touch conflict zone geographies must be considered, particularly those that are incompatible with the firm's values and aims, including those of their stakeholders.